From precision interventions to precision health - Schork, Nicholas J.; Goetz, Laura H. (Nature communications, 2025)
Precision medicines, or those medicines that are tailored to individual genetic, molecular, physiologic, behavioral, and/or exposure profiles, are being developed at a rapid pace. However, just how precise these interventions are in terms of their mechanisms of action (MOAs), clinical effects, and utility in different individuals, are hard anticipate with current preclinical research and clinical trials strategies. To understand how various genes, processes, organs, clinical phenotypes, etc. may be impacted by an intervention, as well as how many people might benefit from it, appropriate data on living human beings needs to be collected as part of built-for-purpose clinical trials. We consider the shift from broad, population-level medicine to ultra-precise, individualized medicine using emerging therapeutic constructs, AI, deep phenotyping, and individual-centered trials to optimize health across diverse individual genetic and physiological profiles.